Pengaruh Metode Latihan Sirkuit Dan Madu Terhadap Kemampuan Vo2 Max Atlet Bulutangkis Universitas Negeri Padang - Muhammad Muhammad Arnando; Syafruddin Syafruddin; Nurul Ihsan; Desi Novita Sari (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
The purpose of this research is to design a circuit method training program and the addition of natural energy ingredients, namely honey, to see its effect on the VO2 Max ability of UNP badminton athletes. There are many training methods to improve the athlete's VO2 Max ability, one of which is the circuit method. This type of research is experimental. This research was conducted at the UNP Badminton Court. The sample in this study amounted to 20 people. To measure the ability of VO2 Max is to use a multistage fitness test (bleep test). Hypothesis testing in this study was processed using descriptive and ineferential statistics with the sample-dependent comparative formula (t-test). Before the data is processed using the t test. From the results of the data analyzed using statistics, it can be concluded that the results of the hypothesis are as follows: There is a significant effect of Circuit Training Method without Honey on the VO2 Max Ability of Badminton Athletes where tcount = 14.18 and ttable (α = 0.05) = 2, 26 and the mean difference is 2.41. There is a Significant Effect of Circuit Training Method plus Honey on the VO2 Max Ability of Badminton Athletes where it is obtained that tcount = 22.61 and ttable (α = 0.05) = 2.26 and the average difference is 5.20. There is a difference in the effect between the circuit training method plus honey and the circuit training method without honey on the VO2 Max Ability of the Badminton Athletes in the Padang State University Sport Activity Unit where tcount = 6.28 and ttable (α = 0.05) = 2.26 and the average difference the average count is 2.45. From the results of the analysis, it can be concluded that the effect of the circuit training method and honey has an effect on the VO2 Max ability of badminton athletes at the Padang State University Sports Activity Unit.